2016
DOI: 10.3389/fnhum.2016.00339
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Processing and the Matching-Stimulus Interval Effect in ERP Components: An Exploration of the Mechanism Using Multiple Regression

Abstract: In oddball tasks, increasing the time between stimuli within a particular condition (target-to-target interval, TTI; nontarget-to-nontarget interval, NNI) systematically enhances N1, P2, and P300 event-related potential (ERP) component amplitudes. This study examined the mechanism underpinning these effects in ERP components recorded from 28 adults who completed a conventional three-tone oddball task. Bivariate correlations, partial correlations and multiple regression explored component changes due to precedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
1
5
2
Order By: Relevance
“…Surprisingly, the enhancement of the P3 amplitude was observed following all three interference types, independent of WM load. Whereas P3 modulations are typically associated with task-difficulty (Kok, 2001) or stimulus probability (Duncan- Johnson and Donchin, 1977), this observation, in turn, indicates that the time interval between stimuli modulates the P3 amplitude (Gonsalvez and Polich, 2002;Steiner et al, 2013Steiner et al, , 2016. In detail, longer intervals between stimuli have been shown to produce greater P3 amplitudes (Steiner et al, 2013) which fits our results of larger P3 amplitudes particularly after distractions and prolonged fixation crosses that did not require a response.…”
Section: Discussionsupporting
confidence: 83%
“…Surprisingly, the enhancement of the P3 amplitude was observed following all three interference types, independent of WM load. Whereas P3 modulations are typically associated with task-difficulty (Kok, 2001) or stimulus probability (Duncan- Johnson and Donchin, 1977), this observation, in turn, indicates that the time interval between stimuli modulates the P3 amplitude (Gonsalvez and Polich, 2002;Steiner et al, 2013Steiner et al, , 2016. In detail, longer intervals between stimuli have been shown to produce greater P3 amplitudes (Steiner et al, 2013) which fits our results of larger P3 amplitudes particularly after distractions and prolonged fixation crosses that did not require a response.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, in line with views that assume a role of working memory, this linear trend did not continue indefinitely, but halted after 5–6 standards. This pattern is in conflict to other studies that reported a linear effect, including one that examined relatively long target‐to‐target intervals (Steiner, Barry, et al., 2016). The latter study differed from the present paradigm in stimulus modality (auditory vs. visual) and the inclusion of task‐irrelevant distractors in the oddball sequence, which could be reasons for the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding should be regarded as preliminary, because the trial numbers in which targets followed very long sequences of standards were low (Table 2). However, visual inspection of data from other studies also descriptively speak for possible cubic trends (Steiner, Barry, et al., 2016, Figure 3; Steiner, Brennan, Gonsalvez, & Barry, 2013, Figure 3), so a systematic examination of potential cubic effects of preceding standards on P300 should be a focus of future research. Such a pattern could thus imply that after very long successions of standards, participants stop “awaiting” a target, or that there are variations in attentional focus or motivational state over the course of successions of standards that affect P300 amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative view on the frequency effect is given by the fact that low frequencies of P3‐evoking target stimuli, in many cases, come along with larger time intervals between targets. A number of studies attempted at disentangling this confound in the oddball task and demonstrated that the time interval between targets is a strong predictor for P3b amplitude effects, both for targets (Gonsalvez & Polich, ; Polich & Bondurant, ; Polich & Margala, ; Steiner, Barry, & Gonsalvez, ) and for non‐targets (at least if targets and non‐targets are equally frequent: Steiner, Barry, & Gonsalvez, , ). Moreover, when standard stimuli to be ignored are not presented at all, which transforms the oddball task into a single‐stimulus paradigm , P3b amplitudes still get larger with increasing interval from the previous target (Croft, Gonsalvez, Gabriel, & Barry, ; Gonsalvez, Barry, Rushby, & Polich, ; Steiner, Barry, & Gonsalvez, ), although the few stimuli presented are no longer rare stimuli among frequent distractors.…”
Section: Experimental Variables: Effects Of Frequency and Relevancementioning
confidence: 99%